Spatial variability of airborne radar reflectivity and velocity measurements of tropical rain with application to spaceborne radar - Stephen L. Durden (AIMS Electronics and Electrical Engineering, 2019)
One of the challenges in accurate estimation of rainfall from spaceborne radars is achievement of adequate spatial resolution with reasonable-sized antennas. Previous studies have shown that variability of precipitation within the radar beam can result in errors in rainfall and Doppler estimation from spaceborne radars. In designing these radars, it is therefore necessary to achieve a spatial resolution that reduces such errors to acceptable levels. In this work the author considers data acquired by airborne radar in the tropics or sub-tropics, over ocean. The author confirms many of the findings of previous studies, specifically large Ku-band reflectivity fluctuations and relatively short Ku-band reflectivity correlation lengths in convective areas. This study also examines similar statistics for Ku-band path integrated attenuation and for vertical motion, the latter of which is not widely discussed in the literature. Results from these observations are then applied to spatial resolution considerations for future spaceborne precipitation radars.